What is a cycling race simulation anyway: a review on protocols to assess durability in cycling - Peeters, W. M.; Barrett, M.; Podlogar, T. (European Journal of Applied Physiology, 2025)
Physiological resilience or durability is now recognised as a determinant of endurance performance such as road cycling. Reliable, ecologically valid and standardised performance tests in laboratory-based cycling protocols have to be established to investigate mechanisms underpinning, and interventions improving durability. This review aims to provide an overview of available race simulation protocols in the literature and examines its rigour around themes that influence durability including (i) exercise intensity anchoring and (ii) carbohydrate intake whilst also (iii) inspecting reliability and justification of the developed protocols. Using a systematic search approach, 48 articles were identified that met our criteria as a cycling race simulation. Most protocols presented limitations to be recommended as exercise test to investigate durability, such as not appropriately addressing the influence of exercise intensity domains by anchoring exercise intensity as % peak power or % VO2max. Ten articles provided reliability data, but only one articles under the appropriate conditions. Most studies sufficiently controlled nutrition during trials but not in the days leading to the trials or just before the trials. Thus, there is a paucity in protocols that combine justification and reliability with optimal nutritional support and mimic the true demands of a road-cycling race. This review lists an overview of protocols that researchers could use with caution to select a protocol for future experiments, but encourages further development of improved protocols, including utilisation of virtual software applications.